TO DEVELOP THE QUALITIES OF RESPONSIBILITY AND INITIATIVE IN CHILDHOOD IS THE PERIOD OF ACUIRING THE STANDARDS OF HUMAN SOCIAL LIFE (Web of Teachers: Inderscience Research, 2025)
Childhood is one of the most important stages of human life, and in this period, the child develops his personality and social life. When entering social life, children follow a number of norms: they must build friendships. It includes many aspects, such as understanding the rules and developing relationships. In this article, the processes of the formation of a child as a person and finding a place in social life are analyzed in this article.